Molecular Docking and Molecular Dynamics Simulation using Monascus sp. as a Candidate Cervical Cancer Drug - Anna Yuliana; Ira Rahmiyani; Cindi Kartika (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
Cervical cancer is the fourth most common female cancer worldwide and results in over 300000 deaths globally. Given that HPV prophylactic vaccines do not exert a therapeutic effect in individuals previously infected, it is unlikely that HPV-associated cancers will be eradicated in the coming years. Therefore, there is an emerging need for the development of anti-HPV drugs. The purpose of this study is to find out Monascus sp. as cervical anticancer using molecular docking and dynamics methods. The results of docked with AutodockTools were visualized with Pymol, analyzed the effectiveness using the Ramachandran plot. The docking results show that there are 2 pigments that have lower G than raloxifen in estrogen receptor beta with the lowest G indicated by the pigment Monascin and Ankaflavin, which is -6.94 kcal/mol with Ki value of 39.49 nM and -6.22 kcal/mol with Ki value of 27.78 nM. The results of molecular dynamics, Ankaflavin and Monascin have good stability at estrogen receptor beta because the outlier area has a value 11.722% and 10.256%. And the amino acid residues in the most preferred area were 68.864% and 70.330%. In addition, Monascopyridine B and Monascuspiloin pigments showed good and stable results at the EGFR receptor because the outlier areas were 14.692% and 10.623%. And the amino acid residues in the most-favored region were 65.403% and 73.260%. Based on the results of this study, we predict that Ankaflavin, Monascin, Monascopyridine B and Monascuspiloin can be used as new cervical anticancer candidates after validated with in vitro and in vivo tests.